No Mobile Phobia Phenomenon _ A Review - Behadili, Suhad Faisal; Jabar, Hadeel; Tahlok, Walaa Sami; Abdulsahib, Safa Ahmed (Iraqi Journal for Electrical and Electronic Engineering, 2021)
The No Mobile Phone Phobia or Nomophobia notion is referred to the psychological condition once humans have a fear of being disconnected from mobile phone connectivity. Hence, it is considered as a recent age phobia that emerged nowadays as a consequence of high engagement between people, mobile data, and communication inventions, especially the smart phones. This review is based on earlier observations and current debate such as commonly used techniques that modeling and analyzing this phenomenon like statistical studies. All that in order to possess preferable comprehension concerning human reactions to the speedy technological ubiquitous. Accordingly, humans ought to restrict their utilization of mobile phones instead of prohibiting it, due to the fact that they could not evade the power of technological progression. In that matter, future perspectives would be employing data mining techniques to explore deep knowledge, which represents correlated relationship between the human and the mobile phone.